The Role of Empathic Tendency, Belief in Teaching Competency and Job Satisfaction in Predicting Attitudes towards the Teaching Profession in Primary and Secondary School Teachers - Öner Çelikkaleli; Ahmet Şadan Ökmen (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - Attitude towards the teaching profession functions as an important factor in the successful continuation of the education and training process. In this context, the first aim of the study is to examine teachers' attitudes towards teaching according to gender, education level, experience, and location of the school. Second, it is to reveal whether or not empathic tendency, teaching competence belief, and job satisfaction predict attitudes towards the teaching profession. Materials/methods - In this research, correlational research model, which is one of the quantitative research methods, was used. For these purposes, data were collected from 316 teachers with an average age of 40.34 (SD = 3.15) years old, of which 189 are female (59.8%) and 127 (40.2%) male. The Attitude Scale towards Teaching Profession, Empathic Tendency Scale, Ohio Teacher Self-Efficacy Scale, and the Job Satisfaction Scale were used as the study's data collection tools. Results - According to the first findings obtained from the research, while teachers' attitudes towards teaching did not differ according to gender, education level (primary/secondary school), or school location (urban or rural); they were found to differ according to their length of experience. Accordingly, the attitudes of teachers with a seniority of more than 20 years were shown to be more positive than those with less experience. Second, empathic tendency, belief in teaching self-efficacy, and also job satisfaction were found to positively and significantly predict attitude towards the teaching profession. Conclusion - Within the framework of these findings, it can be said that gender, education level and school location are not determining variables in teachers' attitudes towards the teaching profession. On the other hand, it has been seen that work experience is important in the attitude towards the profession. Finally, it can be said that self-efficacy belief towards the teaching profession and job satisfaction are important variables in the attitude towards teaching. The obtained findings are then discussed, interpreted, and recommendations put forwards in light of the current literature.